2018
DOI: 10.3892/or.2018.6483
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the potential oncogenes in glioblastoma based on bioinformatic analysis and elucidation of the underlying mechanisms

Abstract: Glioblastoma (GBM) is a common malignant tumour in the human brain, but its molecular mechanisms have not been systematically evaluated. The aim of this study was to identify potential key oncogenes associated with the progression of GBM and to elucidate their mechanisms. The gene expression profile of GSE50161, selected from the Gene Expression Omnibus database, was analysed to find cancer-associated genes and gene functions in GBM. In total, 486 differentially expressed genes, including 128 upregulated genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…a meta-analysis, as a large-sample study, has an advantage in addressing this limitation due to its enhanced statistical power (19). Prior meta-analyses have been applied to study tumors to confirm deGs between tumor tissue and normal tissue in glioma (20,21), lung cancer (22), bladder cancer (23), breast cancer (24), osteosarcoma (25), liver cancer (26) and pancreatic cancer (27). In the present study, integrative meta-analysis of expression data (inMeX) was used to conduct a meta-analysis based on 11 qualified microarray datasets, with the aim to identify crucial deGs between Pdac samples and normal pancreatic samples that may serve as biomarkers for Pdac treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…a meta-analysis, as a large-sample study, has an advantage in addressing this limitation due to its enhanced statistical power (19). Prior meta-analyses have been applied to study tumors to confirm deGs between tumor tissue and normal tissue in glioma (20,21), lung cancer (22), bladder cancer (23), breast cancer (24), osteosarcoma (25), liver cancer (26) and pancreatic cancer (27). In the present study, integrative meta-analysis of expression data (inMeX) was used to conduct a meta-analysis based on 11 qualified microarray datasets, with the aim to identify crucial deGs between Pdac samples and normal pancreatic samples that may serve as biomarkers for Pdac treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…pancreatic, colorectal and lung cancers 36, 37 ) and others not (e.g. uveal melanoma 38 , glioblastoma 39 , kidney cancer 40 ). To determine how RAS84 varied across cancer types, we quantified it against all 32 TCGA solid cancers in a pan-cancer analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Wei et al (36) identified deGs regulated by transcription factors in GBM by analyzing the GSe4290 dataset downloaded from the Gene expression omnibus (Geo) database. Zhang et al (37) selected GSe50161 from Geo database to identify potential oncogenes associated with GBM progression. Moreover, liu et al (38) analyzed the glioma gene expression profile dataset GSe4290 for the identification of deGs.…”
Section: Discussionmentioning
confidence: 99%